Dinamika Opini Publik terhadap Undang-Undang Pelindungan Data Pribadi (Kasus Percakapan Media Sosial X) - Dahana, Abyzan Syahadin Bagja (Universitas Gadjah Mada, 2024)
This study aims to describe the dynamics of public opinion in X around the Data Protection Law (UU PDP) that emerged before and after its ratification. Previous research on the UU PDP has only focused on normative juridical aspects but not on public opinion aspects. In fact, research on public opinion is important because public opinion has the power to advocate. This study analyzed 3,374 tweets about the UU PDP published from January 24, 2020, to October 17, 2023. Researchers obtained the data using the scraping method using the Python Twscrape library based on the search keywords “Undang-Undang Pelindungan Data Pribadi